English literacy design for partner school in freedom of learning-independent campus - Victa Sari Dwi Kurniati; Ima Widyastuti; Adhi Kusuma; Poppy Indriyanti; Aura Victoria Noersadono (Universitas Sarjanawiyata Tamansiswa, 2022)
The school coverage expansion of the Teaching Campus – Freedom of Learning-Independent Campus to the junior high schools have done since 2021 in which some Teaching Campus agents were sent to the junior high school level across provinces in Indonesia. As one of the principal goals of the Teaching Campus lays on assisting teacher especially in numeracy and literacy, the literacy is then developed to English literacy. However, due to the missing learning of English in the primary school level, many junior school students face difficulty in understanding English. Thus, it is very urgent to create various ways for facilitating the learning English process among junior high school students. The current community service activity attempts to assist the junior school teacher in designing a practical English learning by designing English worksheets. The design coincided picture-based worksheets since the students still belonged to the true beginner of English. However, the designed worksheets could be used not merely for building the students’ vocabulary inventory but also promoting the affective-humanistic approach and English learning strategies.